Design Features for Linguistically-Mediated Meaning Construction: The Relative Roles of the Linguistic and Conceptual Systems in Subserving the Ideational Function of Language - Evans, Vyvyan (Frontiers in Psychology, 2016)
Recent research in language and cognitive science proposes that the linguistic system evolved to provide an “executive” control system on the evolutionarily more ancient conceptual system (e.g., Barsalou et al. 2008; Bergen 2012; Evans 2009, 2015a, b). In short, the claim is that embodied representations in the linguistic system interface with non-linguistic representations in the conceptual system, facilitating rich meanings, or simulations, enabling linguistically-mediated communication. In this paper I build on these proposals by examining the nature of what I identify as design features for this control system. In particular, I address how the ideational function of language—our ability to deploy linguistic symbols to convey meanings of great complexity—is facilitated. The central proposal of this paper is as follows. The linguistic system of any given language user, of any given linguistic system—spoken or signed—facilitates access to knowledge representation—concepts—in the conceptual system, which subserves this ideational function. In the most general terms, the human meaning-making capacity is underpinned by two distinct, although tightly-coupled representational systems: the conceptual system and the linguistic system. Each system contributes to meaning construction in qualitatively distinct ways. This leads to the first design feature: given that the two systems are representational—they are populated by semantic representations—the nature and function of the representations are qualitatively different. This proposed design feature I term the bifurcation in semantic representation. After all, it stands to reason that if a linguistic system has a different function, vis-à-vis the conceptual system, which is of far greater evolutionary antiquity, then the semantic representations will be complementary, and as such, qualitatively different, reflecting the functional distinctions of the two systems, in collectively giving rise to meaning. I consider the nature of these qualitatively distinct representations. And second, language itself is adapted to the conceptual system—the semantic potential—that it marshals in the meaning construction process. Hence, a linguistic system itself exhibits a bifurcation, in terms of the symbolic resources at its disposal. This design feature I dub the birfucation in linguistic organisation.